A Case of a Vietnam War Veteran with Early-Onset Huntington's Disease. (9th May 2018) - Allen, Rosie; Suo, Ella; Lek, Jeremy; Samuel, Mathew
We report on the case of Simon (his pseudonym). We describe the presentation of early-stage late-onset Huntington's disease (HD) in a man with multiple psychiatric diagnoses. Our clinical problem was 'To what extent are common psychiatric features masking a further diagnosis?' Initially unwilling to be tested for HD, he agreed on condition that it assists with his discharge plan.